EVALUASI IMPLEMENTASI PROGRAM BANTUAN OPERASIONAL SEKOLAH MENENGAH ATAS (BOS SMA) PADA SMA NEGERI 4 PULAU GOROM KABUPATEN SERAM BAGIAN TIMUR PROVINSI MALUKU - Elok Rahmawati (MAP (Jurnal Manajemen dan Administrasi Publik), 2023)
Senior High School Operational Assistance (BOS SMA) is a central government assistance program to provide funding for personnel and non-personnel operating costs for schools sourced from non-physical special allocation funds. One of the factors that influenced the success of the BOS program was the implementation of BOS funds in accordance with BOS technical guidelines and all available resources in the implementation of the BOS program. The purpose of this study is to describe the use of BOS funds and the impact on students in the teaching and learning process of the 2019/2020 school year. This study used descriptive qualitative method. The results showed that the use of BOS funds by schools was in line with BOS guidelines, flexible, efficient, and effective. although in the realization there are still components that have not been implemented because of the priority scale, according to the needs of the school that is flexible.